POLITIK KULTURAL KH. ABDURRAHMAN WAHID DALAM DEMOKRATISASI - , SUBAIDI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cultural politics can be used as an alternative to the institutionalization of democracy in the country that has a pluralistic nation such as Indonesia . Gait Abudurrahman KH Wahid (Gur Dur) can be recognized as part of a form of cultural politics, and one of the figures that reveal the process of democratization in an alternative route to take inspiration from the concept of habitus and doxa theory offered Pierre Bourdieu. Cultural politics shows that democratization as an expression of resistance an actor (agency) within the structure of power through discursive and controversial actions in the space of democracy, the cultural sphere (cultural fields) and the political sphere (political fields) into the arena game (site of the struggles and strategies), which included a scramble and fight a variety of capital (cultural capital, political capital) of the figure, the political elite in power structures in changing or maintaining a doxa. Owned capital determines the style of the game, the success or failure in the race and capital exchange. This can be seen in the reproduction of discourse conducted by Gus Dur in changing doxa. By showing how the gait Gus Dur in mobilizing resistance to doxa in the form of actions that have a unique and controversial provocation that has the capacity inevitably generate controversy, as a form of resistance against the doxa as well as changes in the door to build a set of values and discourse in the fight and counter the status quo and democratic praxis of domination proceduralistic. It is seen that democracy as a form of resistance and change a doxa. From examination of Gus Dur's efforts to develop a set of values and discourse systems are intended to medekonstruksi and reconstruct discourse secretly structural traps that have become standard , it appears that this tilt Controversy discourse that actually allows the actor will be able to uncover and dismantle problem - issue that has not been realized. The key steps are rolling deskribe nodes around it is considered as a process of democratization restraint excited but at the same time it reaches deeper than the conventional methods which are linear. The process of deconstruction and reconstruction of the discourse through controversial measures that key actors, making the transformation of democratic values has been successfully done in